Prospects for inquiry in Delta Urbanism research by design - Arbara, Sophia; Longhin, Elena; Chereni, Simbarashe; Naghibi, Maryam; Iuorio, Luca; Goncalves, Juliana; Hooimeijer , Fransje (Journal of Delta Urbanism, 2023)
The undisputable human influences on the Earth’s system demand an urgent change of ways and transitions in human systems to sustain a healthy society in the future. Addressing the urgent climatic transformations in deltaic areas, this paper is an attempt of the Delta Urbanism research group at TU Delft to set the line for new (integrated) research inquiries by design and investigate fundamental, experimental, and strategic & operational responses to the existing prospects for action as a way to create collaboration between various sectors. These prospects for action are targeted at four critical fronts (climate, urban, governance, cultural) based on trends and challenges that deltaic areas are facing and to which coherent spatial strategies are needed. These fronts together need a research response to enable the making of the delta of the future through the power of interdisciplinary design. This perspective or prospect is established through six lines of inquiry that are elaborated in the paper. The central question is “how can the research field of delta urbanism provide a transformative ‘prospect for action’ to establish strategic pathways toward a resilient Delta future, where assertion and proof are synergized”? The discussion of the six lines of inquiry, which effectively address the four critical fronts, explores how they are poised to deliver fundamental, experimental, and operational outputs for further research and action.